PSYCHOLOGICAL DISTRESS AND JOB SATISFACTION AMONG HEALTH CARE PROFESSIONALS IN POST COVID-19 ERA (Pakistan Journal of Psychology, 2023)
This aim of this research was twofold: First to examine the role of psychological distress in relation to job satisfaction among health care professionals in post COVIDE-19 era. Second to examine the gender difference on the variables of psychological distress and job satisfaction among health care professionals in post COVID-19 era. A sample of 150 health care providers was chosen from various hospitals of Faisalabad and Toba Tek Singh, Pakistan. Psychological distress, and job satisfaction were measured with the use of the Psychological Distress Scale (Kessler et al., 2003) and the Job Satisfaction Scale (Locke, 1976) respectively. The linear regression analysis reveals a significant predictive association between psychological distress and job satisfaction. The independent t-test reveals an insignificant gender difference on the variables of psychological distress and job satisfaction among health care professionals. The study has significant implications for mental health of health care professionals